Withholding of pension funds benefits under the South African Law - Seakamela, Mmopa Queen (My University, 2013)
This study will analyse section 37D of the Pension Funds Act, 24 of 1956. The analysis will also give insight to pension benefits, and how they are afforded special protection by the legislature. Section 37A (1) prohibits the reduction, transfer, cession, pledge or hypothecation of pension benefits. In terms of the Act if a member becomes insolvent, pension benefits are deemed not to form part of the insolvent estate and are thereby protected from erosion by creditors. Section 37C of the Act deems pension benefits payable on the death of a member, subject to certain exceptions, not to form part of the assets of the estate of the deceased member. Section 19 of the Act also serves to protect pension benefits by restricting the manner in which a fund’s assets may be invested.
Thesis (LLM. (Labour Law)) -- University of Limpopo, 2013
Keywords: Pension funds; Pension benefits; Pensions -- Law and legislation -- South Africa; Pension trusts -- Law and legislation -- South Africa; Retirement income -- South Africa